Proceedings of the 48h IEEE Conference on Decision and Control (CDC) Held Jointly With 2009 28th Chinese Control Conference 2009
DOI: 10.1109/cdc.2009.5400787
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the optimality of the cμ-rule with Stochastic Flow Models

Abstract: We revisit, in the context of Stochastic Flow Models (SFMs), a classic scheduling problem for optimally allocating a resource to multiple competing users. For the two-user case, we establish the optimality of the well-known cµ-rule for arbitrary stochastic processes using calculus of variations arguments as well as an Infinitesimal Perturbation Analysis (IPA) approach. The latter allows us to derive an explicit sensitivity estimate of the cost function with respect to a controllable parameter and to further st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 18 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…This result applies to any sample path, leading to the conclusion that θ * = 1 and the cμ-rule is therefore optimal. In order to extend this result to an arbitrary number of queues, we use the setting proposed in the previous section, slightly different from the one in Kebarighotbi and Cassandras (2009), which allows us to re-derive the IPA derivative and the optimality of the cμ-rule in a simpler way. Our result will then be used in the following section as a base step for an inductive argument generalizing the optimality of the cμ-rule to any N > 2 queues while also providing explicit IPA derivatives as performance gradient estimators in other problems where the cμ-rule is no longer optimal.…”
Section: Infinitesimal Perturbation Analysis (Ipa)mentioning
confidence: 98%
See 4 more Smart Citations
“…This result applies to any sample path, leading to the conclusion that θ * = 1 and the cμ-rule is therefore optimal. In order to extend this result to an arbitrary number of queues, we use the setting proposed in the previous section, slightly different from the one in Kebarighotbi and Cassandras (2009), which allows us to re-derive the IPA derivative and the optimality of the cμ-rule in a simpler way. Our result will then be used in the following section as a base step for an inductive argument generalizing the optimality of the cμ-rule to any N > 2 queues while also providing explicit IPA derivatives as performance gradient estimators in other problems where the cμ-rule is no longer optimal.…”
Section: Infinitesimal Perturbation Analysis (Ipa)mentioning
confidence: 98%
“…This was analyzed by Kebarighotbi and Cassandras (2009) where the sample performance function Q(θ) was expressed in terms of a single parameter θ, defined as the fraction of resource capacity allocated to queue 1. An explicit IPA derivative dQ/dθ was derived and it was shown that if c 1 μ 1 > c 2 μ 2 then dQ/dθ < 0.…”
Section: Infinitesimal Perturbation Analysis (Ipa)mentioning
confidence: 99%
See 3 more Smart Citations